NAD Metabolism in Cancer Therapeutics - Yaku, Keisuke; Okabe, Keisuke; Hikosaka, Keisuke; Nakagawa, Takashi (Frontiers in Oncology, 2018)
Cancer cells have a unique energy metabolism for sustaining rapid proliferation. The preference for anaerobic glycolysis under normal oxygen conditions is a unique trait of cancer metabolism and is designated as the Warburg effect. Enhanced glycolysis also supports the generation of nucleotides, amino acids, lipids, and folic acid as the building blocks for cancer cell division. Nicotinamide adenine dinucleotide (NAD) is a co-enzyme that mediates redox reactions in a number of metabolic pathways, including glycolysis. Increased NAD levels enhance glycolysis and fuel cancer cells. In fact, nicotinamide phosphoribosyltransferase (Nampt), a rate-limiting enzyme for NAD synthesis in mammalian cells, is frequently amplified in several cancer cells. In addition, Nampt-specific inhibitors significantly deplete NAD levels and subsequently suppress cancer cell proliferation through inhibition of energy production pathways, such as glycolysis, tricarboxylic acid (TCA) cycle, and oxidative phosphorylation. NAD also serves as a substrate for poly(ADP-ribose) polymerase (PARP), sirtuin, and NAD gylycohydrolase (CD38 and CD157); thus, NAD regulates DNA repair, gene expression, and stress response through these enzymes. Thus, NAD metabolism is implicated in cancer pathogenesis beyond energy metabolism and considered a promising therapeutic target for cancer treatment. In this review, we present recent findings with respect to NAD metabolism and cancer pathogenesis. We also discuss the current and future perspectives regarding the therapeutics that target NAD metabolic pathways.